The Effect of The Problem-Based Learning Model on The Interest and Learning Outcomes of Mathematics of Elementary School Students - I Ketut Suparya; I Nengah Suastika; I Wayan Lasmawan (Jayapangus Press, 2022)
This research aims to: 1) know the difference in interest in learning mathematics between students who follow the problem-based learning model with students who follow conventional learning models, 2) know the difference in mathematics learning outcomes between students who follow the problem-based learning model and students who follow conventional learning models, 3) simultaneously know the differences in learning interests and learning outcomes of mathematics between students who follow the problem-based learning model and students who follow conventional learning models. This study is a quasi-experiment with randomized post-test only control group design. The population of this study is all students in grade V elementary school, cluster XV, Buleleng district. There were 182 students, while the study sample comprised 60 students, comprising 30 students as a control group and 30 students in an experimental group. The research instrument uses questionnaires to measure interest and tests to measure students learning outcomes, which are further analyzed using one-way manova. the results showed: 1) there was a significant difference in the learning interests of students who followed the problem-based learning model with conventional learning, 2) there are significant differences in math learning outcomes that follow problem-based learning models compared to conventional learning, 3) there are differences in learning interests and math learning outcomes of students who follow problem-based learning models and conventional learning. The results of data analysis show that the application of problem-based learning models has a significant influence on students nterests and learning outcomes.